Psychiatric nursing teaching at the Ana Nery School in the first half of the 20th century - Monique da Silva Carvalho; Gizele da Conceição Soares Martins; Nícia Lima Dias; Tânia Cristina Franco Santos; Antonio José Almeida Filho; Maria Angélica Almeida Peres (Universidade Federal de Goias, 2015)
The aim of this study was to describe the teaching of psychiatric nursing at Ana Néri Nursing School (EAN), between 1925 and 1954. Methodology: Socio-historical research whose sources were written documents and the oral statement of an ex-professor. The documentary analysis technique was used for data treatment. Results: For 27 years, the EAN did not introduce students into the psychiatric field due to the mental illness stigma, offering only theoretical disciplines, which were taught by physicians. Later there were theoretical disciplines with practical training in the classroom, and then theoretical disciplines with practice in psychiatric hospitals, taught by nurses. In conclusion, the law 775/49 lead the EAN to qualify a professor and initiate the reformulation of the nursing care provided at the Institute of Psychiatry of the University of Brazil, so as to adjust it to serve as a practical field and a model for teaching psychiatric nursing in Brazil.